Improvement of biogas quality product from dairy cow manure using NaOH and Ca(OH)2 absorbents on horizontal tube filtration system of mobile anaerobic digester. (December 2020) - Herwintono,; Winaya, Aris; Khotimah, Khusnul; Hidayati, Asmah
Abstract: Natrium Hydroxide (NaOH) and Calcium Hydroxide (Ca(OH)2 ) as an absorbent was used in the filtration system of the mobile anaerobic digester (AD) to improve the quality of biogas from dairy cattle manure. Twelve pilots insulated of mobile AD used in this study. The average temperature inside the digester was 28.37 °C, and in the outer digester 27.16 °C. The average biogas temperature before filtration was 28.37 °C, and after filtration 31.09 °C. The biogas filtration using adsorbent was a very significantly effect (P < 0.01) to the digester and biogas temperature. While the measurement time of temperature was very significantly different (P<0.01) to digester temperature but was not different on biogas temperature (P > 0.05). The average biogas production using NaOH was 717.50 mL h −1, Ca(OH)2 715.63 mL h −1, and control 676.25 mL h −1 . The adsorbent treatments were very significantly effects (P<0.01) to biogas production but not significantly different (P > 0.05) among the type of adsorbent. The NaOH could increase the percentage of methane (CH4 ) (14.26 %) and oxygen (O 2 ) (22.06 %) content, and reduced carbon dioxide (CO2 ) (30.86 %) compared with control. However, Ca(OH)2 adsorbent could increase CH4 (7.77 %) and O 2 (11.22 %) and reduced CO2 (17.88 %). The mobile anaerobic digester is suitable for smallholder farmer because more simple and cheaper.